Electron flow through biological molecules: does hole hopping protect proteins from oxidative damage?. Issue 4 (16th July 2015) - Winkler, Jay R.; Gray, Harry B.
Abstract: Biological electron transfers often occur between metal-containing cofactors that are separated by very large molecular distances. Employing photosensitizer-modified iron and copper proteins, we have shown that single-step electron tunneling can occur on nanosecond to microsecond timescales at distances between 15 and 20 Å. We also have shown that charge transport can occur over even longer distances by hole hopping (multistep tunneling) through intervening tyrosines and tryptophans. In this perspective, we advance the hypothesis that such hole hopping through Tyr/Trp chains could protect oxygenase, dioxygenase, and peroxidase enzymes from oxidative damage. In support of this view, by examining the structures of P450 (CYP102A) and 2OG-Fe (TauD) enzymes, we have identified candidate Tyr/Trp chains that could transfer holes from uncoupled high-potential intermediates to reductants in contact with protein surface sites.